2005
DOI: 10.1016/j.febslet.2005.02.077
|View full text |Cite
|
Sign up to set email alerts
|

The N137 and P140 amino acids in the p51 and the P95 amino acid in the p66 subunit of human immunodeficiency virus type 1 (HIV‐1) reverse transcriptase are instrumental to maintain catalytic activity and to design new classes of anti‐HIV‐1 drugs

Abstract: The N137 and P140 amino acids in the p51 and the P95 amino acid in the p66 subunit of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase are instrumental to maintain catalytic activity and to design new classes of anti-HIV-1 drugs Abstract Amino acids N137 and P140 in the p51 subunit of HIV-1 reverse transcriptase (RT) are part of the b7-b8-loop that contributes to the formation of the base of the non-nucleoside RT inhibitor (NNRTI)-binding pocket and makes up a substantial part of the dimerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…Mutations with these two residues might destabilize the RT dimer or interfere with the correct placement of the primer in the active site, leading to a significant decrease in RT activity and therefore viral fitness. Indeed, clinical studies and in vitro mutational analysis have shown that both residues are immutable (Pelemans et al, 2000;Auwerx et al, 2005;Ceccherini-Silberstein et al, 2005), suggesting that compound II's interactions with these two residues will be able to compensate for potential lost interactions due to other NNBP mutations. Moreover, although compound II forms a hydrogen bond with the frequently mutated K103, the hydrogen bond donor is the backbone amide of K103, suggesting that the interaction is likely maintained in a number of K103 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations with these two residues might destabilize the RT dimer or interfere with the correct placement of the primer in the active site, leading to a significant decrease in RT activity and therefore viral fitness. Indeed, clinical studies and in vitro mutational analysis have shown that both residues are immutable (Pelemans et al, 2000;Auwerx et al, 2005;Ceccherini-Silberstein et al, 2005), suggesting that compound II's interactions with these two residues will be able to compensate for potential lost interactions due to other NNBP mutations. Moreover, although compound II forms a hydrogen bond with the frequently mutated K103, the hydrogen bond donor is the backbone amide of K103, suggesting that the interaction is likely maintained in a number of K103 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several amino acid substitutions within the β7-β8 loop of p51 are known to impair heterodimer formation, while decreasing the DNA polymerase activity of the viral RT in enzymatic assays. [16][17][18] Molecular mechanisms leading to fitness recovery play an important role in antiretroviral therapy. Evolution of drug resistance is characterized by severe fitness losses, which can be partially overcome by compensatory mutations or other adaptive changes that restore viral replication capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In p51, residues 52-55 and 135-140 in the fingers subdomain, 255-265 and 286-290 in the thumb subdomain, and 393-402 and 420-423 in the connection subdomain generate the largely hydrophobic surface that interacts with p66. 15 Several non-conservative mutations in p51 that affect residues of the β7-β8 loop (positions 134-139) [16][17][18][19] or the so-called "Trp motif" (residues 398, 401, 402, 406, 410 and 414) 20,21 are known to impair RT dimerization, while producing a loss of viral infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 3= ultimate and penultimate positions of the AS primer were designed to overlap with the first two nucleotides of the E138 codon (see Table S1B in the supplemental material). Intentional mismatches were placed on two invariant adenine nucleotides of residue N137 (27,34,35) to increase the sensitivity. Of note, approximately half of subtype B and subtype C viruses should not have any mutations in the AS primer-binding site (27).…”
Section: Design Of An As-pcr For E138a E138g E138k E138q E138rmentioning
confidence: 99%